Simplified polarization diversity heterodyne receiver for 1.25Gb/s cost-effective udWDM-PON - Cano, Ivan N.; Lerin, Adolfo; Polo, Victor; Prat, Josep (OFC 2014, 2014)
We propose a heterodyne receiver with a single-photodiode per polarization for ONU receiver in low-cost udWDM-PON. This grants polarization diversity operation showing a penalty of 6dB in sensitivity compared to a balanced detector.